Istota i znaczenie konkurencyjności w handlu żywnością oraz perspektywy rozwoju polskich przedsiębiorstw - Michałowska, Mariola (The Essence and Meaning of Competition in Food Trade and Perspectives of Development of Polish Companies, 2006)
Nowadays can observe changes in Polish companies which occur as the result of building of great marketing chains. Management of companies on the competitive market becomes a very complex issue requiring knowledge of rules, methods and marketing instruments.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 100-105